1988
DOI: 10.1111/j.1755-3768.1988.tb04039.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked myopia in danish family

Abstract: X-linked infantile myopia is described in a family of 273 members of whom 87 were examined in the National Eye Clinic. The disease may represent a new ocular syndrome, constituted by myopia combined with astigmatism, impaired vision, hypoplasia of the optic nerve heads, and deuteranopia. Obligate carriers presented slight retinal changes. Linkage studies are in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 8 publications
1
36
2
Order By: Relevance
“…If this were the case, his behavioral phenotype would be expected to be that of a blue cone monochromat. However, he clearly retains M-cone function and phenotypically, his disorder is similar to Bornholm Eye Disease (BED) where a generalised cone dysfunction and protanopia is found alongside myopia (Haim, Fledelius & Skarsholm, 1988, Michaelides et al, 2005, Young et al, 2004). Retinal imaging demonstrates extensive cone depletion, the presence of non-waveguiding cones and an overall thinning of the retina.…”
Section: Discussionmentioning
confidence: 94%
“…If this were the case, his behavioral phenotype would be expected to be that of a blue cone monochromat. However, he clearly retains M-cone function and phenotypically, his disorder is similar to Bornholm Eye Disease (BED) where a generalised cone dysfunction and protanopia is found alongside myopia (Haim, Fledelius & Skarsholm, 1988, Michaelides et al, 2005, Young et al, 2004). Retinal imaging demonstrates extensive cone depletion, the presence of non-waveguiding cones and an overall thinning of the retina.…”
Section: Discussionmentioning
confidence: 94%
“…The second suggestion: High myopia and cone dysfunction are parts of the same syndrome. These disorders have been described earlier Haim et al 1988), and the mode of the inheritance has been x-chromosomal recessive. A colour vision defect of protan type ) and deutan type (Haim et al 1988) has been observed with this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders have been described earlier Haim et al 1988), and the mode of the inheritance has been x-chromosomal recessive. A colour vision defect of protan type ) and deutan type (Haim et al 1988) has been observed with this disorder. The female carrier of the disorder can also show some of the features of the disease: myopia and diminished cone resonse in the ERG examination ) and a unilateral high myopia (Verdoorn &-Pinckers 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The original family mapped to this locus demonstrated syndromic high myopia, characterized by high myopia, cone dysfunction, and color vision deficiency. 80,81 Several additional families with similar phenotypes were identified subsequently. [82][83][84] A large family with nonsyndromic high myopia has been mapped to MYP1.…”
Section: Syndromic High Myopiamentioning
confidence: 97%